2013
DOI: 10.1116/1.4821651
|View full text |Cite
|
Sign up to set email alerts
|

Metal-assisted etching of silicon molds for electroforming

Abstract: Articles you may be interested inVertical directionality-controlled metal-assisted chemical etching for ultrahigh aspect ratio nanoscale structures J. Vac. Sci. Technol. B 32, 06FI01 (2014); 10.1116/1.4898199 Influence of catalytic gold and silver metal nanoparticles on structural, optical, and vibrational properties of silicon nanowires synthesized by metal-assisted chemical etching J. Appl. Phys. 112, 073509 (2012); 10.1063/1.4757009Nanofabrication of x-ray zone plates using ultrananocrystalline diamond mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Increasing the HF concentration further, however, showed a loss of verticality of the etch (due to the irregular catalyst motion mentioned above) as well as increased incidence of delamination of the Au layer (figure 6). This is a typical etch outcome for HF concentrations >4 M. This pattern has been observed elsewhere [10,19] and demonstrates that there is a balance to be maintained in the etching parameters in order to maintain a high aspect ratio etch with an acceptable Si surface quality. An option for reducing porous Si formation may be to conduct the MacEtch under an electric bias [20] which suppresses excessive etching and which may be investigated in future studies.…”
Section: Etching Solutionsupporting
confidence: 76%
“…Increasing the HF concentration further, however, showed a loss of verticality of the etch (due to the irregular catalyst motion mentioned above) as well as increased incidence of delamination of the Au layer (figure 6). This is a typical etch outcome for HF concentrations >4 M. This pattern has been observed elsewhere [10,19] and demonstrates that there is a balance to be maintained in the etching parameters in order to maintain a high aspect ratio etch with an acceptable Si surface quality. An option for reducing porous Si formation may be to conduct the MacEtch under an electric bias [20] which suppresses excessive etching and which may be investigated in future studies.…”
Section: Etching Solutionsupporting
confidence: 76%
“…[18][19][20] A Ti interlayer between Au catalyst layer and Si substrate was previously introduced as a conventional adhesion layer, and these paper reported that the Ti interlayer helped to eliminate the unnecessary lateral Si etching during MacEtch. 21,22) However, the detail of role for Ti interlayer in MacEtch process has not been fully understood. Therefore, in this study, the usefulness of a metal interlayer interposed between the metal catalyst and Si is demonstrated for the formation of vertical microscale holes in a Si(100) substrate by MacEtch, and the effect of the interlayer is investigated and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[8]. Some of these problems have been overcome, for example by post‐partum sonication treatment [16], etchant formulation control [8, 16, 18], changing etch bath [16], using by‐layer catalyst [16, 19], and controlling deposition rate and thickness of catalyst [17].…”
Section: Introductionmentioning
confidence: 99%